2021
DOI: 10.1111/tpj.15200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and epigenetic analysis reveals that NAC transcription factors regulate fruit flavor ester biosynthesis

Abstract: Flavor-associated volatile chemicals make major contributions to consumers' perception of fruits. Although great progress has been made in establishing the metabolic pathways associated with volatile synthesis, much less is known about the regulation of those pathways. Knowledge of how those pathways are regulated would greatly facilitate efforts to improve flavor. Volatile esters are major contributors to fruity flavor notes in many species, providing a good model to investigate the regulation of volatile syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 57 publications
4
76
0
Order By: Relevance
“…A lot of attention has been paid to the role of the NAC gene family members during fruit development and ripening. A recent study found that PpNAC1 regulated the expression of ripening-related PpAAT1 and contributed to volatile ester formation in Prunus persica [60], indicating a key role during fruit ripening. In papaya (Carica papaya), CpNAC1 was reported to regulate carotenoid accumulation during fruit ripening [61].…”
Section: Discussionmentioning
confidence: 98%
“…A lot of attention has been paid to the role of the NAC gene family members during fruit development and ripening. A recent study found that PpNAC1 regulated the expression of ripening-related PpAAT1 and contributed to volatile ester formation in Prunus persica [60], indicating a key role during fruit ripening. In papaya (Carica papaya), CpNAC1 was reported to regulate carotenoid accumulation during fruit ripening [61].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in banana, MabZIP4 and MabZIP5 were capable of binding directly to BanAAT promoter, suggesting the function of MabZIPs in controlling aroma production [ 42 ]. Additionally, the transcription factor PpNAC1 was proved to transcriptionally activate the PpAAT1 gene and formation of volatile esters in peaches [ 44 ]. AP2/ERF transcription factors have been shown to be associated with the production of volatile terpenes in sweet orange fruits [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In peach fruits (Prunus persica), PpNAC1 promotes the biosynthesis of volatile esters during fruit ripening by directly binding to the promoter region of alkyl transferase alcohol acyltransferase 1 (PpAAT1) and activating its expression. This pathway is downstream of ethylene signal and conserved in tomato (SlNOR-SlAAT1) and apple fruit (MdNAC5-MdAAT1) [144].…”
Section: Nac Tfs and Accumulation Of Fruit Flavor Compoundsmentioning
confidence: 99%